2015
DOI: 10.1016/j.yebeh.2015.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral predictors of medication adherence trajectories among youth with newly diagnosed epilepsy

Abstract: Objective This study aimed to identify psychosocial predictors of two-year antiepileptic drug (AED) adherence trajectories among youth with newly diagnosed epilepsy, controlling for known demographic and medical factors. Method This study is part of a large, prospective, longitudinal observational study of AED adherence and medical outcomes in youth with newly diagnosed epilepsy. Parents completed questionnaires of psychosocial and family functioning at one-month and one-year following diagnosis. Chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…We did not gather information about the adequacy of the prescribed antiseizure drug treatments. Patients taking medication more frequently are less likely to be adherent compared to patients taking extended-release or once a day formulations 36,55,67. This and many other factors, from tablet color to treatment affordability, may have had an impact in the adherence that has yet to be measured.…”
Section: Discussionmentioning
confidence: 99%
“…We did not gather information about the adequacy of the prescribed antiseizure drug treatments. Patients taking medication more frequently are less likely to be adherent compared to patients taking extended-release or once a day formulations 36,55,67. This and many other factors, from tablet color to treatment affordability, may have had an impact in the adherence that has yet to be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Generally there are several factors that can influence medication adherence to AEDs in adolescents including regimen complexity or their beliefs about medication as they may stop taking the medication because they do not want to be viewed as being different than others [12]. Research on children population has revealed that disliking the taste of medication, running out of medications [13], parent forgetfulness, refusal to take medications [13,14], difficulties in swallowing the medication [14], lower socioeconomic status [15][16][17] and family conflict and difficulties in communication particularly during adolescence [17] were barriers to adherence to AEDS. Poor adherence to prescribed AEDs is associated with negative consequences such as reduced seizure control [18][19][20], higher incidence of hospital admissions [20][21][22] and increased health care costs [5,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Acceptability of/participation in the recommended treatment regime. Psychosocial factors are associated with medication non-adherence, for example, following acute coronary syndrome [51], in haemodialysis patients [52], in youth with newly diagnosed epilepsy [53]. One systematic review of study of psychosocial factors predicting non-adherence to preventative maintenance medication therapy produced a negative result and call for more research [54].…”
Section: Emerging Evidence Of Psychosocial Causationmentioning
confidence: 99%